Pinus vallartensis (Pinaceae), a new species from western Jalisco, Mexico - de La Rosa, Jorge A. Pérez; Gernandt, David S. (Phytotaxa, 2017)
We propose and describe Pinus vallartensis Pérez de la Rosa & Gernandt as a new species from western Jalisco, Mexico. The pine occurs near the southern limit of the Sierra Occidental at the intersection of the municipalities of Puerto Vallarta, Cabo Corrientes, and Talpa de Allende. Pinus oocarpa occurs within the margins of this forest to the south and P. jaliscana to the west. The more distantly related pine, P. maximinoi, also occurs in the area. Pinus vallartensis is like P. jaliscana and P. oocarpa in possessing leaf resin canals in a septal condition and serotinous seed cones on slender peduncles. It is distinguished mainly by its small seed cones and lax foliage. This discovery highlights the exceptional diversity of pines in Mexico and the state of Jalisco.